Shy Willow - Min, Cat (Levine Querido, 2021)
"Willow is shy. VERY shy. Her home is in an abandoned mailbox, and she'd rather stay put. Outside kids scream and soccer balls collide, trees look like monsters, and rain is noisy in a scary kind of way. It's much nicer to stay inside, drawing. But then a young boy drops a letter in Willow's mailbox: it's a note to the moon asking for a special favor. Willow knows that if she doesn't brave the world outside, the letter will never be delivered, and the boy will be heartbroken. Should she try? Can she?"--Provided by publisher